Two new species and new records of Syndicus Motschulsky (Coleoptera, Staphylinidae, Scydmaeninae) from SE Asia and Australia - Jałoszyński, Paweł (Zootaxa, 2014)
Two new species of the cyrtoscydmine ant-like stone beetle genus Syndicus are described: S. (s. str.) birmanicus sp. n. (from Myanmar) and S. (Semisyndicus) chiangmaianus sp. n. (from Thailand). A previously unknown male of S. (s. str.) puncticollis Jałoszyński is described, and for the first time the spermatheca of S. (Semisyndicus) sumatrensis Schaufuss is illustrated. Syndicus puncticollis, S. (s. str.) difficilis Jałoszyński, and S. (s. str.) saketianus Jałoszyński, all previously known only from Thailand, are recorded for the first time from Myanmar. Additionally new records are given for S. (s. str.) lamdongianus Jałoszyński (from Laos), S. (s. str.) kingii (King) (from Australia), S. (s. str.) malandae Franz (from Australia), and S. (Semisyndicus) leai ranongianus Jałoszyński (from Thailand).